Implementación y administración de un servidor de dominio, mediante Segurity Account Manager para centralizar los recursos, servicios de las TIC´S del Gad Municipal del cantón Mejía. - Collahuazo Quinatoa, María Belén (2020)
At ICT Municipal GAD department of Mejia Canton there is no a domain server, since they work in a traditional way, users are interconnected to a network, because of this the equipment is not manageable generating delay in the process of the creation of users, units of organization and computer equipment, for this reason this research project proposes to provide a solution to the computer resources administration, through an Active Directory, allowing organize groups to manage and protect equipment resources, In order to control and safeguard the users information of the GAD, different methodologies were applied for the extraction and deduction of solutions, carrying out an analysis of the necessary qualities that the domain server must have and put into practice through an experimental model . As a result, centralized control of computer resources users and equipment was obtained, thus avoiding various problems on the network: such as unauthorized access to resources by outsiders and loss of labor information from the institution. It is concluded that with the domain server users accounts could be managed, group and teams, thus giving an organization of ICT resources and services to the Municipal GAD.